Prevalence of risk factors for Non-communicable diseases, work-related health problems and associated factors among male three-wheeler drivers in Gampaha Urban Council area, Sri Lanka - Dissanayake SAIP; Kisokanth G; Warnakulasuriya SSP (Journal of Men's Health, 2021)
Background and objective: Driving is associated with various occupational health problems and the nature of the job creates a greater risk for Non-communicable diseases (NCDs) among the drivers. We aimed to determine the prevalence of risk factors for NCDs, work-related health problems and its associated factors among three-wheeler drivers in Gampaha Urban Council area, Western Province, Sri Lanka. Methods: A descriptive cross-sectional study was carried out among 289 randomly selected three-wheeler drivers. A pre-tested, validated interviewer administered questionnaire was used to collect data. Descriptive and relevant inferential statistics were used to analyze data by using SPSS v20. Binary logistic regression was used to identify the factors associated with common work-related health problems. Results: Among all participants, 80% were using alcoholic beverages, 35% of them were currently smoking and 39% of them had the habit of betel chewing. The mean body mass index (BMI) and waist circumference (WC) of the participants were 25.28 (±4.37) kg/m2 and 92.17 (±11.61) cm respectively. The prevalence of work-related health problems among the participants were low back pain (35%, 95% CI = 29.78–40.80), hypertension (32%, 95% CI = 33.14–44.37), obesity based on BMI (30%, 95% CI = 24.49–35.03). Working experience of ≥10 years (AOR = 2.29, 95% CI = 1.16–4.51), sitting for ≥6 hours/day during driving (AOR = 2.23, 95% CI = 1.03–4.82), not following regular exercise (AOR = 2.54, 95% CI = 1.02–6.37), having snacks ≥ twice/day (AOR = 3.06, 95% CI = 1.52–6.18) and WC ≥90 cm (AOR = 37.00, 95% CI = 11.00–123.99) were the factors associated with obesity. Conclusion: Tobacco and alcohol use, high BMI, inadequate physical activity, and unhealthy eating habits were found as the major risk factors for NCDs among three-wheeler drivers. The prevalence of work-related health problems was relatively high and job characteristics were the major determinant of most health problems.